2021
DOI: 10.21123/bsj.2021.18.1.0047
|View full text |Cite
|
Sign up to set email alerts
|

Various Extracts of Some Medicinal Plants as Inhibitors for Beta-lactamase Activity

Abstract: The inhibitory effect of acetone, ethanol, and aqueous extracts of ten medicinal plants on β-lactamase from Staphylococcus sciuri and Klebsiella pneumoniae was investigated in vitro by starch-iodine agar plate method. The results revealed the success of starch-iodine method for the detection of the inhibition of β-lactamase activity by the various extracts of each individual plant. The acetone extracts of Catharanthus roseus, Eucalyptus camaldulensis, and Schinus terebinthifolius induced an inhibitory effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…Sophora flavescens root samples purchased from local markets in Baghdad city were identified by a botanist (specialist in plant taxonomy in the Department of Biology/College of Science for women. Aqueous extracts of S. flavescens root were prepared according to Al-Hayanni and El-Shora (2021). Soak the dried root powder (60 g) with 600 mL distilled water (DW) for 3 h. To create an aqueous extract, the extraction solutions were filtrated with filter paper (Whatman No.…”
Section: Preparation Of S Flavescens Root Aqueous Extractmentioning
confidence: 99%
“…Sophora flavescens root samples purchased from local markets in Baghdad city were identified by a botanist (specialist in plant taxonomy in the Department of Biology/College of Science for women. Aqueous extracts of S. flavescens root were prepared according to Al-Hayanni and El-Shora (2021). Soak the dried root powder (60 g) with 600 mL distilled water (DW) for 3 h. To create an aqueous extract, the extraction solutions were filtrated with filter paper (Whatman No.…”
Section: Preparation Of S Flavescens Root Aqueous Extractmentioning
confidence: 99%
“…The results showed that the extracts have some oxidative activity and that this activity has a synergistic effect on the antioxidant effect of DPPH radical. The high contents of total phenolic, total flavonoid, and tannin compounds in H. salicornicum and Z. coccineum alcoholic extracts can contribute to important antioxidants because of the strong relationship between the concentration of the compounds (27) . The phenolic extraction and the effectiveness of antioxidants, which showed that these compounds are mostly to charge as they are effective antioxidants has a polar nature (28) .…”
Section: Discussionmentioning
confidence: 99%
“…and identified by the Department of Biology/ College of Science for women. Aqueous and ethanol extracts of the Sumac fruit were prepared according to (11,12). with some modifications: by drenching 50 g each of the dry grind plant materials in 500 ml of solvent (distilled water in aqueous extract) and in 250 ml of solvent (ethanol in alcohol extract) at room temperature for 48 hrs.…”
Section: Methodsmentioning
confidence: 99%